Conocimientos y prácticas sobre alimentación en la mujer gestante, que acude al Hospital Universitario Motupe. - Bravo Heras, María del Cisne (2017)
In pregnancy the feeding, has great influence in the health results of the fetus and the mother. This investigation has the purpose to identify the knowledge and feeding practices of pregnant women. This study was of type descriptive and cross-sectional in a sample of 100 pregnant women. And the data were obtained using a survey, it was applied to pregnant women that attended to Hospital Universitario de Motupe, during the period March - July of 2016, where the following results: the 82% have a high degree of knowledge about the importance and function of the different nutrients in feeding during pregnancy. The overall assessment of food practices showed that pregnant women did not perform the appropriate practices; specifically only 4% eat more than 3 meals a day, in daily food consumption of macroronutrient sources, was identified that 38% consume carbohydrates, 16% fruits and vegetables, 7% lipids (omega 3 source foods) and only 4% consume protein, of micronutrients only calcium is consumed daily by 48% while iron and folic acid are not, and the total population indicated, they have not consumed dangerous substances to pregnancy. In conclusion, pregnant women know the importance and function of food, but they do not perform any adequate food practices. Keywords: feeding, pregnant women, knowledge, practices